Achieving urban food and nutrition security in the developing world: Overview - Garrett, James L. (International Food Policy Research Institute, 2000)
The trend is inescapable: more and more people in the developing world are living in the cities. By 2020, the number of people living in developing countries will grow from 4.9 billion to 6.8 billion. Ninety percent of this increase will be in rapidly expanding cities and towns. More than half the population of Africa and Asia will live in urban areas by 2020. More than three-quarters of Latin Americans already do. Growth in urban poverty, food insecurity, and malnutrition and a shift in their concentration from rural to urban areas will acompany urbanization.... urban poverty, food insecurity, and malnutrition are problems of today, not tomorrow. -- from Text